Cybersecurity Risk Management: Integrating Technology And Digital Security Awareness: English - Ni Wayan Lasmi; Komang Widhya Sedana Putra P; Wayan Sri Maitri (International Journal of Economics, Science, and Education, 2026)
Purpose: This study examines how cybersecurity resilience can be strengthened by integrating technological capabilities and human factors. Specifically, it explores the role of cybersecurity technology and digital security awareness in enhancing cybersecurity risk management, using a combined perspective of the Technology Acceptance Model (TAM) and Resource-Based View (RBV). Design/methodology/approach: A quantitative approach was employed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). Data were collected from digital companies operating in Denpasar to test the proposed relationships and moderating effects. Findings: The results indicate that cybersecurity technology significantly improves cybersecurity risk management. In addition, digital security awareness strengthens this relationship, suggesting that higher awareness enhances the effectiveness of technological tools. Research limitations/implications: The study is limited by its focus on a single geographic area and a cross-sectional design, which may limit broader applicability. Future research is encouraged to involve multiple regions and longitudinal data. Practical implications: Organizations should not rely solely on technological investments but also prioritize improving employees’ digital security awareness to achieve stronger cybersecurity resilience. Originality/value: This study contributes by integrating TAM and RBV to highlight the interaction between technological and human capabilities in cybersecurity risk management. Paper type: Research paper